Virtual Reality Tourism Application: Insights from Tourism Enterprises (Critical Journal of Social Sciences, 2026)
In a context of robust digital change within the tourism sector, virtual reality tourism has emerged as a promising trend to augment the tourist experience and facilitate enterprises in innovating their business models. This study seeks to assess the extent of access to and experience with virtual reality tourism among tourism enterprises in Ho Chi Minh City, while also reflecting strategies to enhance the implementation of this technology in the industry. The research employed a quantitative survey involving 100 representatives from tourism enterprises in Ho Chi Minh City. The findings demonstrate that businesses view virtual reality tourism favorably and have access to a range of virtual reality tourism options via various platforms. Companies also concur that virtual reality tourism is a useful tool for promoting tourism, improving experiences, and creating new tourism-related products. The study suggests management implications to encourage tourism businesses to increase awareness, access, and application of virtual reality tourism more successfully.